A Spatial related Note on Entrepreneurship and Economic Growth - Torben Klarl (European Regional Science Association (ERSA), 2011)
A large and still growing body of literature suggests that entrepreneurship is of exceptional importance in explaining regional specific efficiencies of knowledge spillovers. Although quantifying the impact of entrepreneurial activity for economic growth is an interesting issue – particularly at the regional level – a consice formulation within a theoretical growth model is missing. This paper in general tries to uncover the link between own- and neighbour-related regional entrepreneurial activity in innovation and regional growth within a spatial semi-endogenous growth model in the spirit of Jones (1995) reflecting recent empirical findings on entrepreneurial activity for economic growth. The paper makes the following points: firstly, the degree of tacit knowledge spillover within the R&D-sector is positively related to own and neigbhour-related entrepreneurial activity and secondly, for a given entrepreneur's willingness to invest in R&D-projects the degree of tacit knowledge spillover is higher with stronger institutions. The paper derives an explicit solution for the transitional as well as for the balanced growth path level of entrepreneurs' innovative activities.
Keywords: 330